Exploring Physical Force and Subject Resistance in Police Encounters with People with Behavioral Health Issues. Issue 8 (17th November 2018) - Gill, Charlotte; Jensen, Rachel; Cave, Breanne
ABSTRACT: The interaction between police use of force and subject resistance or noncompliance is particularly complex in cases involving people with behavioral health issues (PBHI). Using three years of incident reports (2014–2016) and an officer survey from a midsize suburban police department, the authors explore this interaction and officers' experiences and perceptions of encounters with PBHI. They find that police are less likely to use physical force in cases involving PBHI, even in the face of more, and more severe, resistance. However, officers believe they use force more frequently and are unsatisfied with the options available to them to address behavioral health challenges. The authors conclude with recommendations for police training and practice.